Book Review: "Islam and the Secular State: Negotiating the Future of Sharia" - Ririn Noviyanti (MAQASHID, 2018)
The development of modern thought in Islam, is a distinct dynamism in the intellectual space, which is never discussed, because the development of this thought is the intellectual muddle of the earlier Islamic thinkers, which is then passed on to the next generation, as the times and the times progress. So when discussing of contemporary Islamic thinkers, it would seem odd to forget the figure of Abdullah Ahmed Al-Na'im, who allegedly included a rare thinker and a scholarly dedication to be reckoned with in the contemporary world of contemplation. Which not only fathers on the matter of worship mahdhoh, ethics, etc. However, he is an activist who possesses a high degree of popular loyalty without prejudice to his criticism of political, legal and governmental matters. This is proven through affilia-tion in human rights institutions, although the figure of Ahmed Al-Na'im is also a brilliant academic figure. Sharia always has a bright future in the public life of Islamic soci-ety because it can play a role in preparing the generations for the life of society, fostering institutions and social relations and so forth. Sharia will continue to play an important role in shaping and developing ethical norms and values that can be reflected in public legislation and policies through a democratic political process. Muslims everywhere, whether as majority or minority, are required to practice Islamic sharia as part of their religious obligations. But according to the author the principles or rules of sharia cannot be applied and applied formally by the state as law and public policy only for the reason that the principles and rules are part of sharia. In addition, the main target of this book is Muslims everywhere, but not monolithic, remarkable, or static categories of readers. Intellectual and professional Muslims, who tend to be the ruling elite and opinion-maker in their society, are largely shaped by the European style of education, which allows them to appreciate philosophical concepts and terms that may be unknown to those educated in traditional Islamic schools (madrasah).